Elevated serum cardiac markers in asymptomatic marathon runners after competition: is the myocardium stunned? - Siegel, A. J.; Sholar, M.; Yang, J.; Dhanak, E.; Lewandrowski, K. B. (Cardiology, 1997)
Prolonged strenuous exercise may trigger acute myocardial infarction (AMI), as exemplified by the occurrence of sudden cardiac death during marathon running. Serum creatine kinase MB (CK-MB) may be elevated in asymptomatic marathon runners after competition from exertional rhabdomyolysis of skeletal muscle altered by training, limiting its utility for evaluating acute cardiac injury in such athletes. Myoglobin and CK-MB2 isoform levels are emerging as earlier markers of AMI and troponin subunits as more specific than serum CK-MB mass. We tested runners before and sequentially after the 1995 Boston Marathon for conventional and newer markers including myoglobin, CK-MB mass and isoforms, cardiac troponin T, and cardiac troponin I using standard laboratory methods and rapid format assays if available. The mean serum values for myoglobin, CK-MB mass, CK-MB/myoglobin rapid panel tests, and CK-MB2 isoforms were normal or negative pre-race and elevated or positive 4 and 24 h after competition. These markers lack specificity for acute cardiac injury in trained runners. While the mean serum values for cardiac troponins T and I remained normal, 9 of 45 runners (20%) showed an increase in subunits by first-generation assays. All runners remained asymptomatic for cardiac disease and completed subsequent marathons 1 year later, making reversible myocardial injury or stunning unlikely. Elevated values of serum markers for AMI, including first-generation assays for both troponin subunits should be interpreted with caution in trained runners.